2016
DOI: 10.1007/s00497-016-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics resources for pollen

Abstract: Bioinformatics for Pollen. Pollen plays a key role in crop production, and its development is the most delicate phase in reproduction. Different metabolic pathways are involved in pollen development, and changes in the level of some metabolites, as well as responses to stress, are correlated with the reduction in pollen viability, leading consequently to a decrease in the fruit production. However, studies on pollen may be hard because gamete development and fertilization are complex processes that occur durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 172 publications
(203 reference statements)
0
3
0
Order By: Relevance
“…Our results are consistent with earlier studies b a that found that bee-collected pollen showed a significant increase in O 2 uptake relative to ungerminated pollen (Keularts and Linskens 1968;Verhoef and Hoekstra 2012), supporting retained metabolic activity despite absence of pollen tube formation. Future studies of early germination processes (e.g., through the use of Ca 2+ flux ((Steinhorst and Kudla 2013), structural cellular changes (Vogler et al 2015), and transcriptomics and proteomics (Ambrosino et al 2016)) may provide additional understanding of pollen digestion in this species. By investigating these earlystage cellular components and processes in the honey bee gut, future studies may yield additional information that cannot be captured in studies of pollen tube formation or fertilization potential alone.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with earlier studies b a that found that bee-collected pollen showed a significant increase in O 2 uptake relative to ungerminated pollen (Keularts and Linskens 1968;Verhoef and Hoekstra 2012), supporting retained metabolic activity despite absence of pollen tube formation. Future studies of early germination processes (e.g., through the use of Ca 2+ flux ((Steinhorst and Kudla 2013), structural cellular changes (Vogler et al 2015), and transcriptomics and proteomics (Ambrosino et al 2016)) may provide additional understanding of pollen digestion in this species. By investigating these earlystage cellular components and processes in the honey bee gut, future studies may yield additional information that cannot be captured in studies of pollen tube formation or fertilization potential alone.…”
Section: Discussionmentioning
confidence: 99%
“…The list of the resources here presented (Table 6), in comparison to the variety of studies on different plants and stress types, and the limited number of integrated platforms dedicated to abiotic stresses, highlights that, although the spreading of advanced molecular technologies and novel challenging projects in the field (e.g., [353]), coordinated and completed efforts that could provide data and information resources for further investigations and mining in the field are still strongly required [354]. Table 6.…”
Section: Dedicated Web Based Resourcesmentioning
confidence: 99%
“…Mesihovic et al (2016) provide guidelines for terminologies and experimental designs, which are of importance to unify information and to perform future experiments in a more standardized fashion, and Ambrosino et al (2016) gives an overview at which places public available information can be found. Finally, what emerges is the need to integrate new large-scale datasets to extract key components of pollen vitality and to apply this knowledge to guide new breeding strategies, which is outlined in the article by Driedonks et al (2016).…”
mentioning
confidence: 99%